Military and school personnel psychological states amidst the Pandemic: A Kruskal-Wallis comparative analysis - Fernandez, Aldwin Roy L.; Laud-Iligan, Hanna Grace; Relleve, Cesar Chester O. (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2023)
Purpose – This study aims to determine the Compassion Satisfaction, Burnout, and Secondary Traumatic Stress among Military and School Personnel.Method - Quantitative descriptive-comparative research design was used. There are 147 respondents participated in this study.Result - Compassion Satisfaction levels of Military-Enlisted and Teaching Personnel were Average, while for the Military-Officer and Non-Teaching School Personnel were High; Burnout for the Military-Enlisted and Teaching Personnel were both Average, while the Military-Officer and Non-Teaching School Personnel were both low; and the Secondary Traumatic Stress was Low for the Military-Officer and Average to other three groups of respondents. Significant differences manifested after employing the parametric test MANOVA and non-parametric Kruskal-Wallis. Post Hoc test was employed in order to identify the specific significant differences.Implication – The researchers have identified significant pattern and trends that contribute to the understanding of comparison, personnel who are less often directly exposed to the clients have better Psychological States descriptively.Originality - This research contributes to the existing body of knowledge in the areas of Compassion, Burnout and Stress experienced by militaries and educators in the conduct of their respective public services.***Tujuan - Penelitian ini bertujuan untuk mengetahui Kepuasan Belas Kasih, Burnout, dan Stres Trauma Sekunder di antara Personel Militer dan Sekolah, serta untuk membandingkan kondisi-kondisi psikologis tersebut.Metode - Desain penelitian deskriptif-komparatif kuantitatif digunakan. Ada 147 responden yang berpartisipasi dalam penelitian ini.Hasil - Tingkat Kepuasan Belas Kasih pada Tamtama Militer dan Tenaga Pengajar tergolong sedang, sedangkan pada Perwira Militer dan Tenaga Kependidikan tergolong tinggi; Burnout pada Tamtama Militer dan Tenaga Pengajar tergolong sedang, sedangkan pada Perwira Militer dan Tenaga Kependidikan tergolong rendah; dan Stres Traumatis Sekunder tergolong rendah pada Tamtama Militer dan tergolong sedang pada tiga kelompok responden lainnya. Perbedaan yang signifikan terlihat setelah menggunakan uji parametrik MANOVA dan non parametrik Kruskal-Wallis. Uji Post Hoc digunakan untuk mengidentifikasi perbedaan signifikan yang spesifik,Implikasi - Para peneliti telah mengidentifikasi pola dan tren signifikan yang berkontribusi pada pemahaman perbandingan, personel yang lebih jarang terpapar langsung dengan klien memiliki kondisi psikologis yang lebih baik secara deskriptif.Orisinalitas - Penelitian ini berkontribusi pada pengetahuan yang sudah ada di bidang Welas Asih, Kelelahan dan Stres yang dialami oleh militer dan pendidik dalam melaksanakan layanan publik masing-masing.